2020
DOI: 10.3390/md18050272
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Inhibitory and Antifouling Activities of New Bromotyrosine Metabolites from the Polynesian Sponge Pseudoceratina n. sp.

Abstract: Four new brominated tyrosine metabolites, aplyzanzines C–F (1–4), were isolated from the French Polynesian sponge Pseudoceratina n. sp., along with the two known 2-aminoimidazolic derivatives, purealidin A (5) and 6, previously isolated, respectively, from the sponges Psammaplysilla purpurea and Verongula sp. Their structures were assigned based on the interpretation of their NMR and HRMS data. The compounds exhibited quorum sensing inhibition (QSi) and antifouling activities against several strains of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…After early reports of isolation and characterization of such bromotyrosines as 3,5-dibromoverongiaquinol and the dimethyl ketal from two verongiid sponges Verongia fistularis and V. cauliformis in 1967 [ 52 , 53 ] and 1970 [ 54 ], numerous experimental and review reports concerning extraction, identification, biosynthesis, synthesis and modifications as well as practical applications of bromotyrosines of verongiids’ origin have been published (see for overview [ 20 , 55 64 ]). If the multitarget functionality of the biological action of bromotyrosines and their high pharmacological potential are no longer in doubt, the strategies for their extraction from biological raw materials or the development of key ways of efficient and inexpensive synthesis of corresponding analogous substances remain a controversial point.…”
Section: Introductionmentioning
confidence: 99%
“…After early reports of isolation and characterization of such bromotyrosines as 3,5-dibromoverongiaquinol and the dimethyl ketal from two verongiid sponges Verongia fistularis and V. cauliformis in 1967 [ 52 , 53 ] and 1970 [ 54 ], numerous experimental and review reports concerning extraction, identification, biosynthesis, synthesis and modifications as well as practical applications of bromotyrosines of verongiids’ origin have been published (see for overview [ 20 , 55 64 ]). If the multitarget functionality of the biological action of bromotyrosines and their high pharmacological potential are no longer in doubt, the strategies for their extraction from biological raw materials or the development of key ways of efficient and inexpensive synthesis of corresponding analogous substances remain a controversial point.…”
Section: Introductionmentioning
confidence: 99%
“…For example, effective antifoulants against barnacles and microfoulants (Oguri et al 2017) have been found in the red alga Laurencia sp. (Oguri et al 2017), tunicates (Levert et al 2020), the mollusk Phidiana militaris (Levert et al 2020), holothurians (Kamyab et al 2020), and sponges (Tintillier et al 2020). Antifoulants may improve the success of marine invasive tunicates (Utermann et al 2020;Nagai et al 2021).…”
Section: Chemical Defensementioning
confidence: 99%
“…This represents a comprehensive list of all secondary metabolites isolated from Verongiida sponges within the period from 1960 to May 2020. It is important to note that since May 2020 to August 2021, a further 7 papers have been published concerning secondary metabolites from this order that were not included in this analysis [ 176 , 177 , 178 , 179 , 180 , 181 , 182 ]. A full reference list can be found in Supporting Information S1 .…”
Section: Methodsmentioning
confidence: 99%